Niger : Joint Staff Advisory Note on the Second Poverty Reduction Strategy Paper. (IMF Staff Country Reports; Country Report, 2008)
This Joint Staff Advisory Note (JSAN) reviews the Second Accelerated Development and Poverty Reduction Strategy (SDARP) of Niger, which provides a framework for implementing the government's growth and poverty reduction agenda. It provides a thorough poverty diagnosis, sectoral plans, policy reforms for achieving the MDGs, and also examines the risks to its implementation. The review assesses that success of the strategy requires strong political commitment for sustained implementation of reforms and programs, aimed at increasing productivity and investment, improving governance, and ensuring macroeconomic stability. It also stressed the need to monitor the strategy implementation.